2006
DOI: 10.1227/01.neu.0000197104.78684.5d
|View full text |Cite
|
Sign up to set email alerts
|

Medial Sphenoid Wing Meningiomas: Clinical Outcome and Recurrence Rate

Abstract: Group 1 meningiomas present a more favorable subgroup with fortunate visual outcome. In Group 2 tumors, visual improvement was less favorable and radical removal is limited because of cavernous sinus infiltration, with consequential higher recurrence rates. Patients harboring recurrent Group 2 tumors with deteriorating visual function profit from microsurgery because vision can be preserved on the same preoperative level in the majority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 23 publications
4
136
1
3
Order By: Relevance
“…The surgical treatment for recurrence tumor was even more difficult than that in the first time operation (20). In our series, 14 patients had undergone surgery in other center and experienced recurrence, the rate of total removal (71.4%) was lower than the patients performed the first operation (83.2%).…”
Section: Liu D Et Al: Large Medial Sphenoid Wing Meningiomasmentioning
confidence: 64%
See 3 more Smart Citations
“…The surgical treatment for recurrence tumor was even more difficult than that in the first time operation (20). In our series, 14 patients had undergone surgery in other center and experienced recurrence, the rate of total removal (71.4%) was lower than the patients performed the first operation (83.2%).…”
Section: Liu D Et Al: Large Medial Sphenoid Wing Meningiomasmentioning
confidence: 64%
“…In small tumors it was usually accessible, while, in large or giant tumors, the tumor infiltrate wildly and more difficulty may be encountered to remove all of the dural and bony attachments radically which may increase the risk of injury of neural structure and exposure-induced complications. Nakanuma et al (20) found that there was no statistically difference of recurrence rate between group with bone removal and group without removal. We considered that heavy coagulation of dural can maybe kill most of even all of the tumor cells and can replace radically resection if no signs of erosion of bone inspected at the surgery and images.…”
Section: Correlation Of Tumor Size With Clinical Characteristics and mentioning
confidence: 94%
See 2 more Smart Citations
“…Even if a large bony segment is removed, there will be no need to make a bony reconstruction soon (4). Whatever the type of the sphenoid wing meningioma, the authors invariably report the trick of the surgical technique as removal of the sphenoid wing after providing a good anatomical orientation for SOF and the related area (10,15,19,24,27).…”
Section: Discussionmentioning
confidence: 99%